Optimization of solid waste management in a metropolitan city. (2021) - Saxena, Sumit; Rajendran, Chandrasekharan; Sanjeevi, V.; Shahabudeen, P.
Abstract: The aim of this research is to optimize the total cost (collection and transportation) of solid waste management. The study presents a mixed integer linear programming model which deals with minimization of total collection and transportation cost of solid waste management. The model is solved by applying to case study in a metropolitan city. Numerical representation for the model is presented to understand the model. The proposed model overcomes the limitations of existing work.